증발 조건에서 초고압 분사와 노즐 홀 직경이 디젤 유량 및 분무 특성에 미치는 영향에 대한 연구 - 조원규; Won Kyu Cho; 박영수; Young Soo Park; 배충식; Choong Sik Bae; 유준; Jun Yu; 김영호; Young Ho Kim (한국분무공학회지, 2015)
Experimental study was conducted to investigate the effects of ultra-high injection pressure and nozzle hole diameter on diesel flow and spray characteristics. Electronically controlled ultra-high pressure fuel injection system was made to supply the fuel of ultra-high pressure consistently. Three injection pressures, 80, 160, and 250MPa were applied. Four type of injec- tors with identical eight nozzle holes were used. The four injectors have nozzle hole diameters of 115, 105, 95, and 85μm respectively. Injection quantity and rate were measured to investigate flow characteristics according to injection pressures and nozzle hole diameters. Mie-scattering and shadowgraph were performed to visualize liquid and vapor phases of diesel spray in a constant volume combustion chamber (CVCC). Ambient conditions of high pressure and high temperature in a diesel engine were simulated by using CVCC.